Muscle enzyme release does not predict muscle function impairment after triathlon - Margaritis, I.; Tessier, F.; Verdera, F.; Bermon, S.; Marconnet, P. (The Journal of Sports Medicine and Physical Fitness, 1999)
BACKGROUND: We sought to determine the effects of a long distance triathlon (4 km swim, 120 km bike-ride, and 30 km run) on the four-day kinetics of the biochemical markers of muscle damage, and whether they were quantitatively linked with muscle function impairment and soreness. METHODS: Experimental design: Data were collected from 2 days before until 4 days after the completion of the race. Participants: Twelve triathletes performed the triathlon and five did not. Measures: Maximal voluntary contraction (MVC), muscle soreness (DOMS) and total serum CK, CK-MB, LDH, AST and ALT activities were assessed. RESULTS: Significant changes after triathlon completion were found for all muscle damage indirect markers over time (p < 0.0001). MVC of the knee extensor and flexor muscles decreased over time (p < 0.05). There is disparity in the time point at which peak values where reached for DOMS, MVC and enzyme leakage. There is no correlation between serum enzyme leakage, DOMS and MVC impairment which occur after triathlon. CONCLUSIONS: Long distance triathlon race caused muscle damage, but extent, as well as muscle recovery cannot be evaluated by the magnitude of changes in serum enzyme activities. Muscle enzyme release cannot be used to predict the magnitude of the muscle function impairment caused by muscle damage.